2015
DOI: 10.5152/tjg.2015.0139
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch repair gene expression in gastroesophageal cancers

Abstract: Background/Aims: Mismatch repair (MMR) genes play a critical role in maintaining genomic stability, and the impairment of MMR machinery is associated with different human cancers, mainly colorectal cancer. The purpose of our study was to analyze gene expression patterns of three MMR genes (MSH2, MHS6, and EXO1) in gastroesophageal cancers, a pathology in which the contribution of DNA repair genes remains essentially unclear. Materials and Methods: A total of 45 Romanian patients diagnosed with sporadic gastroe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Previous studies have found a clear correlation between ASF1B expression and immune cell infiltration, affecting tumor progression by altering immune infiltration. [ 23 ] It is suggested that ASF1B may promote cancer cell proliferation by altering the immune microenvironment of STAD. In addition, we found that TMB and MSI were positively correlated with ASF1B expression, with the high ASF1B expression group showing higher tumor heterogeneity, which was generally associated with impaired immunity and poorer survival.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found a clear correlation between ASF1B expression and immune cell infiltration, affecting tumor progression by altering immune infiltration. [ 23 ] It is suggested that ASF1B may promote cancer cell proliferation by altering the immune microenvironment of STAD. In addition, we found that TMB and MSI were positively correlated with ASF1B expression, with the high ASF1B expression group showing higher tumor heterogeneity, which was generally associated with impaired immunity and poorer survival.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in accordance with other studies showing increased expression of MSH2 in cancers such as gastric cancer. 79,80 The increased expression of MSH2 in fibroid tumors as compared to adjacent myometrium samples may be due to several possible mechanisms. It is possible that increased expression of MSH2 could be a cellular adaption for DNA lesion repair.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation may be that the increased expression of MSH2 could represent a possible response to the rapidly growing number of replication errors in the fibroid tissue with an increased rate of cell divisions. 79,80 Moreover, MSH2 levels can be reduced by ubiquitin-proteasome pathway. 81 Since PRC has been shown to regulate several DNA repair genes, we performed experiment to determine whether EZH2 regulates MSH2 expression.…”
Section: Discussionmentioning
confidence: 99%